A longitudinal study of risk factors for suicide attempts among Operation Enduring Freedom and Operation Iraqi Freedom veterans. Issue 7 (10th April 2018) - Lee, Daniel J.; Kearns, Jaclyn C.; Wisco, Blair E.; Green, Jonathan D.; Gradus, Jaimie L.; Sloan, Denise M.; Nock, Matthew K.; Rosen, Raymond C.; Keane, Terence M.; Marx, Brian P.
Abstract : Background: Suicide rates among veterans have increased markedly since the onset of Operations Enduring Freedom (OEF) and Iraqi Freedom (OIF; LeardMann et al., 2013). Identification of factors with the greatest contribution to suicide risk among veterans is needed to inform risk assessment and to identify intervention targets. Methods: This study examined predictors of suicide attempts among participants in the Veterans After‐Discharge Longitudinal Registry; a nationwide cohort of OEF/OIF veterans enrolled in Department of Veterans Affairs (VA) services. Veterans with and without probable posttraumatic stress disorder (PTSD) were sampled at a 3:1 ratio, and male and female veterans were sampled at a 1:1 ratio. Participants ( N  = 1, 649) were assessed at two time points, roughly 2 years apart ( M  = 28.74 months, SD  = 8.72). Results: Seventy‐four participants (4.49%) attempted suicide during the follow‐up period. The strongest predictors of suicide attempts among the full sample were suicidal intent, attempt history, suicide ideation, PTSD symptoms, alcohol use disorder (AUD) symptoms, and depression. Veterans with multiple risk factors were particularly vulnerable; of veterans with 0, ≥1, ≥2, ≥3, or ≥ 4 of these risk factors, 0%, 7.81%, 10.31%, 18.45%, and 20.51% made a suicide attempt, respectively. Conclusions: This prospective study identified several strong predictors of suicide attempts among OEF/OIF veterans which may be important targets for suicide prevention efforts. Further, co‐occurrence of multiple risk factors was associated with markedly greater risk for suicide attempts; veterans with multiple risk factors appear to be at the highest risk among OEF/OIF veterans enrolled in VA care.